The Mediating Effect of Debt Equity Ratio on The Effect of Current Ratio, Return on Equity and Total Asset Turnover on Price to Book Value - Colline, Fredella (University of Merdeka Malang, 2022)
The research conducted here has two aims: firstly, it endeavors to examine the impacts of liquidity, Profitability, and activity ratio on capital structure as well as the firm value; and, secondly, it attempts to examine the role of capital structure as a mediator. We conduct the test with multiple regression and path analysis over 2020 – 2021 quarterly, with Eviews 8 software. Some companies in the technology sector are taken as samples. Besides, we also analyze financial statement data from Indonesia Stock Exchange. The result indicates Current Ratio, Return on Equity, Debt Equity Ratio significantly affect the Price Book Value, while Total Asset Turnover does not. The Current Ratio does not significantly affect the Debt Equity Ratio, while Total Asset Turnover and Return on Equity have significant negative effects. Path Analysis has confirmed that the Debt Equity Ratio cannot mediate the effect of the Current Ratio and Return on Equity on Price Book Value. However, it fully mediates the effect of Total Asset Turnover on Price Book Value. This finding of the present study supports the pecking order and static theory. The novelty of this research is that there is still little research on debt equity ratio as a mediator. There is no research especially on the technology sector, using those factors to determine the firm value. This research also uses the latest data of financial statements.